Remington 1894 - Johnstone, William W.; Johnstone, J. A. (Remington, 2017)
After the Butcher gang invades his ranch in Arizona Territory and kills his family, aging ex-Civil War sniper John McMasters sets out to take revenge on them in the only way he knows how--with his trusty Remington shotgun.